Pengembangan Rancangan Aplikasi Hear Talk Me untuk di Gunakan Penyandang Tunarungu Berbasis Sistem Operasi Android - Rakhmadi Rahman; Muhammad Aril; Ananda Nabila Putri (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
With all respect and gratitude, we express our gratitude to the presence of Allah SWT who has bestowed His grace and grace, so that we can complete a paper entitled "Development of Hear Talk Me Application Design for Deaf People Based on the Android operating system". Shalawat and salam may always be poured out to the Prophet Muhammad SAW, a role model for mankind. This paper describes the development of smarthphone aids that aim to improve accessibility for deaf people. This application is designed using the android operating system to be easily used by users with special needs. The main features included include text to voice translation and vice versa, as well as vibration notifications for incoming calls or messages. With this paper, we hope to create a useful and effective tool for deaf people to be able to access and utilize Smartphone functions maximally, hopefully this paper can provide useful insights and inspire further research in the development of accessibility technology